An Active Rectifier With Pulse Width Modulation (PWM) Mode On- and Off-Delay Compensation for Wireless Power Transfer (WPT) System - Kaishan Zheng; Ying Hou; Xiaosong Wang; Yu Liu (IEEE Access, 2023)
In this article, an active rectifier with pulse width modulation (PWM) mode on- and off-delay compensation technique is proposed. Conventional delay compensation modes: current mode, voltage mode, and delay-based mode are discussed respectively. Also, the adaptive delay compensation technique and potential disturbance problems are analyzed. To achieve wide and flexible delay compensation range, the proposed rectifier adopts current mode delay compensation methods to eliminate on- and off-delay. Moreover, PWM mode feedback loops are built to compensate circuit delays adaptively under various process, voltage, and temperature (PVT) and loading conditions. Compared with previous works, the proposed PWM mode technique converts the fluctuant error voltages into the fixed duty cycle signal in each cycle, avoiding the disturbance on compensation current and even error flips of comparators. The stability of the current compensation is improved. The proposed active rectifier was designed and fabricated in $0.18μ \text{m}$ CMOS process. Both TX and RX coils are designed and fabricated on printed circuit board (PCB), and the diameter is limited below 3cm. Measurement results show that, with the input sine voltage amplitude ranging from 1.5V to 2.4V and 2MHz operating frequency, the peak power conversion efficiency (PCE) achieves 91.7% under $200Ω $ loading resistor and the peak voltage conversion ratio (VCR) achieves 93.7% with $500Ω $ loading resistor. The maximum output power reaches 57.6 mW. Compared with the case with no PWM mode delay compensation, the measurement PCE and VCR are improved by at least 9%. The proposed rectifier achieves better dynamic performance and is suitable for wireless power transfer (WPT).